Hydrogeology and Vulnerability to Pollution of Carbonate Aquifers in the High Valley of the Basento River (Lucanian Apennines, Southern Italy) - Muzzillo, Rosalba; Pascale, Stefania; Sdao, Francesco (Journal of Environmental Accounting and Management, 2026)
The aim of the present study is the evaluation of the intrinsic vulnerability to pollution of one of the major carbonate aquifer systems of the Basilicata region, Southern Italy. This aquifer system is represented by the wide Arioso-Pierfaone morphostructure, located in the higher sector of the Basento Valley, and characterized by abundant groundwater resources, quantified in about 10 Mm3/yr flowing from several springs. Many of these are captured, though not fully exploited, whereas others are not captured, though characterized by considerable discharges. From a structural point of view, the study area is characterized by the presence of numerous faults and thrusts. As a consequence, the permeability of the carbonate aquifer system shows a large variability. The choice of the methodological approach for the evaluation of the vulnerability has been based on the local hydrogeological characteristics and on the amount of available geological information. In particular, the evaluation of the intrinsic vulnerability of the Basento Valley carbonate aquifer system was obtained using the “SINTACS” point count system model. This method allowed to evaluate that the six classes of the intrinsic vulnerability of the carbonate system vary between very low and very high. High values of vulnerability are due to the density of the fractures, the distribution of the outcropping lithologies, the petrographic composition of the permeated geological formations and the depth of the piezometric surface.